First record for Peru of Nematophila grandis (Diesing, 1839) Travassos, 1934 (Trematoda, Diplodiscidae) in Podocnemis unifilis (Troschel, 1848) (Testudines, Pelomedusidae) - Salízar, Patricia (2004)
The present work registers for the first time for the Peru to Nematophila grandis (Diesing, 1839) Travassos, 1934 in the Yellow-spotted River Turtle Podocnemis unifilis «taricaya». The hosts were collected from the localities of the River Putumayo, Samiria, Iquitos (Loreto) and Manu (Madre de Dios). Identified material was deposited in the Helmintological Collection of the Department of Protozoology, Helmintology and Relationed Invertebrates of the Natural History Museum of San Marcos University.